Strengthening the management and productivity of waste bank through organic waste processing to support green economy in Ngargogondo Village, Magelang Regency - Joko Tri Nugraha; Shefa Dwijayanti Ramadani; Ari Mukti; Choirin Nashiroh; Fauzan Muhammad Rizqullah (Community Empowerment, 2024)
A green economy in rural areas requires effective and sustainable waste management strategies to reduce environmental impact and improve community welfare. The Dahlia Waste Bank in Ngargogondo Village, Magelang Regency, faces challenges in enhancing management quality and productivity, particularly in organic waste processing. This community service program aims to strengthen the management of the Dahlia Waste Bank through training in processing organic waste into economically valuable compost, education on waste management based on the 4R principles (refuse, reduce, reuse, recycle), and the introduction of innovative waste processing technologies. This program employs a community empowerment approach to increase awareness, responsibility, and active participation in waste management. The program outcomes show a significant increase in the amount of waste processed into compost and improved waste bank management quality. Additionally, it has successfully expanded the community's understanding of the importance of waste management as part of the green economy, resulting in reduced environmental damage risks and enhanced local welfare.